Teleworking: gender inequality in evidence: - Amaral de Moura, Janaína (2024)
This article problematizes some of the effects of teleworking, adopted sincethe Covid-19 pandemic, on the lives of female employees at the Court of Justice of theState of Rio de Janeiro (TJRJ). This is an exploratory and qualitative study, with openended interviews. The responses were analyzed and systematized by content analysis. The systematized material was examined in light of the critical social theory of historical-dialectical materialism. The reports pointed to an increase in the demand for reproductive and productive work in the daily lives of civil servants, with additional physical, emotional and even financial costs in teleworking performance. The condition imposed by the unequal sexual division of domestic work also led to situations of family conflict. The responses suggested that their health condition had worsened, so that it was possible to infer that the experience of teleworking increased gender inequality in the researched group.